2003
DOI: 10.1073/pnas.1031698100
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the anorectic fatty acid synthase inhibitor C75 on neuronal activity in the hypothalamus and brainstem

Abstract: c-fos ͉ arcuate nucleus ͉ paraventricular nucleus ͉ lateral hypothalamic area ͉ nucleus of the solitary tract͞area postrema P eripheral neural and hormonal signals that indicate global energy status are monitored in several regions of the brain, notably the hypothalamus and brainstem (1, 2). Within the hypothalamus, three interconnected regions, i.e., the arcuate nucleus (Arc), paraventricular nucleus (PVN), and lateral hypothalamic area (LHA), play important roles in regulating food intake and energy expendit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
62
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(69 citation statements)
references
References 24 publications
6
62
0
1
Order By: Relevance
“…The expression of these neuropeptides is under the control of hormonal and nutritional signals (7)(8)(9)(10)(11)(12). More recently, it has been suggested that the precursors and break-down products of the fatty acid synthesis may be important metabolic signals regulating hypothalamic neuropeptides (10,13,14). The pathway of lipogenesis de novo and the hypothalamic levels of malonyl-CoA have been also identified as a key intermediate controlling food intake.…”
mentioning
confidence: 99%
“…The expression of these neuropeptides is under the control of hormonal and nutritional signals (7)(8)(9)(10)(11)(12). More recently, it has been suggested that the precursors and break-down products of the fatty acid synthesis may be important metabolic signals regulating hypothalamic neuropeptides (10,13,14). The pathway of lipogenesis de novo and the hypothalamic levels of malonyl-CoA have been also identified as a key intermediate controlling food intake.…”
mentioning
confidence: 99%
“…However, C75 also decreased feeding and body weight when administered into the brain by intracerebroventricular (i.c.v.) injection, 4,26,40,41 at doses considerably lower than effective peripheral doses, suggesting that C75 interacted directly with the brain to alter food intake. Although high doses of peripherally injected C75 produced conditioned taste aversion and other indices of malaise in rats, 42,43 C75 given i.c.v.…”
Section: C75: Food Intake Body Weight and Hypothalamic Neuropeptide mentioning
confidence: 99%
“…Our interest in hypothalamic AMPK grew from our work with C75. General brain injection of C75 in rodents decreases food intake and body weight, 4,26,40,41 so C75 exerts some of its weight loss effects by acting in CNS. Once we knew that C75 altered pAMPK in neurons in vitro, 8 we altered the brain and hypothalamic AMPK in mice using well-known pharmacological tools, and fed and fasted states, to demonstrate that AMPK was a physiological mediator of C75's effects.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, central administration of C75, a potent inhibitor of FAS, also increases malonyl-CoA concentration in the hypothalamus, suppresses food intake and leads to profound weight loss (Gao and Lane, 2003). It has been proposed that centrally, C75 and cerulenin -another inhibitor of FAS -alter the expression profiles of feeding-related neuropeptides (such as NPY), often inhibiting the expression of orexigenic peptides (Gao and Lane, 2003). C75 also increases energy consumption, which contributes to weight loss.…”
Section: Hypothalamic Sensing Of Lcfas and Metabolic Syndromementioning
confidence: 99%
“…The molecular mechanisms relaying fatty acid action involve metabolites such as acylCoA or malonylCoA, which could be major fuel sensors and most of the enzymes involved in lipid metabolism are detected at high level in the hypothalamic nucleus that control feeding behavior like the ARC, DMN and VMN (Kim et al, 2002;Sorensen et al, 2002). Moreover, central administration of C75, a potent inhibitor of FAS, also increases malonyl-CoA concentration in the hypothalamus, suppresses food intake and leads to profound weight loss (Gao and Lane, 2003). It has been proposed that centrally, C75 and cerulenin -another inhibitor of FAS -alter the expression profiles of feeding-related neuropeptides (such as NPY), often inhibiting the expression of orexigenic peptides (Gao and Lane, 2003).…”
Section: Hypothalamic Sensing Of Lcfas and Metabolic Syndromementioning
confidence: 99%